Modified Glass Carbon Electrode (GCE) Electropolymerized Polypyrrole Nanofibers with Hemoglobin (Hb) Film as a Unique Biosensor for Nitrite Determination - mohamad Ali zare (Journal of Optoelectronical Nanostructures, 2020)
Abstract: In this study, we were investigated behavior the electrochemical reductionof nitrite at a hemoglobin (Hb) immobilized on glass carbon electrode (GCE) containingpolypyrol nanofiber (ppy) films. Polypyrrole (PPy) nanofibers have been constructed onGCE applying electrochemical technique, and can to deposit diverse polymers onminiaturized electrodes with this common method. The structure of the acquiredelectrode and the electrochemical behavior were characterized using Scanning ElectronMicroscopy (SEM), Cyclic Voltammetry (CV), and Linear Sweep Voltammetry (LSV).The immobilized Hb showed an irreversible reduction peak with a formal potential of –0.72 versus Ag/AgCl, in 0.1M pH 4.5 acetate buffer. The immobilized Hb exhibitedremarkable electrocatalytic activity for the reduction of nitrite. Under the optimalcondition the nitrite concentrations range 2.0×10−4 to 46.0×10−4 M with a detection limitof 6.2×10−5 M (at S/N=3). The resulting biosensor has been successfully applied to thedetermination of nitrite in water samples. The produced modified electrode for nitritedetermination has been explored within the presence of the interfering substancesincluding a number of common ions and cations, demonstrating great selectivity.